Emotional experiences of indigenous children during hospitalization. a qualitative approach to cultural gaps - Esteves Villanueva, Ángela Rosario; Incacutipa Limachi, Duverly Joao; Incacutipa Limachi, Cleida; Aparicio Salas, Vilma Luz (Escuela Profesional de Ciencias de la Comunicación Social de la Universidad Nacional del Altiplano, 2021)
The emotional reactions of indigenous children need to be addressed from an intercultural health approach, because they are motivated by cultural patterns that differ from the hospital system. The objective is to interpret the emotional reactions of indigenous children in hospitalization. The research was carried out using the qualitative approach of an interpretive ethnographic type, carried out in a public hospital with 23 indigenous children hospitalized in the pediatric area, through in-depth interviews. The results reflect the misunderstanding of cultural codes / fear of abandonment, rebellion to the instructions of health personnel, fear of procedures, sleep disorders. We come to the conclusion that the Aymara and Quechua hospitalized child, due to the cultural context of origin, faces a disadvantageous relationship in the hospital, expressed in the misunderstanding of hospital codes on the part of the children and cultural codes on the part of the hospital staff. For this reason, it is essential to recognize the cultural and ethnic diversity and multilingualism of patients during specialized care with an appropriate and inclusive social approach.